Reflections on the Church and HIV/AIDS: South Africa - Haddad, Beverley (Theology today, 2005)
The church in South Africa faces a new challenge—the HIV/AIDS pandemic, which claims the lives of people in its communities and congregations every day. Until recently, the church remained silent or, worse still, adopted a theology that contributed to the stigma and discrimination faced by those who are HIV-positive. Increasingly, this theology is being questioned, as church leaders take a more positive public stance on education, prevention, care, support, and lobbying for treatment. Yet a mainstream, contextual theology that acknowledges and supports people living with HIV/AIDS, offering them Christian hope and acceptance, still remains to be formulated for South Africa.